XOR JÁMÁÁTINIŃ ATQARÍWSHÍLÍQ UQÍBÍ HÁM QÁBILETI - Bekpolatova, A. (SCIENCE and SOCIETY, 2023)
An important role in the conducting process is played by the conductor's face, his eyes, and facial expressions. Modern conducting requires from the conductor musical theoretical training, fine ear, good musical memory, as well as active, purposeful will. A conductor must be able to combine the individualities of individual musicians in the process of conducting, directing all their efforts to the implementation of their performing plan.